La antropología redescubre la sexualidad: un comentario teórico - Vance, Carole S. (El Colegio de México A.C., 1997)
Despite its reputation for openness to research on sexuality anthropology as a discipline has only reluctantly supported such work. Anthropological research and theory developed slowly, sharing a stable theoretical paradigm (the cultural influence model) from the 1920's to the 1990's. Moving beyong determinist and essentialist frameworks still common in biomedicine, anthropological work nevertheless viewed important aspects of sexuality as universal and transcultural.Social construction theory has offered a challenge to traditional anthropological models and has been responsible for a recent burst of innovative work in sexuality, both in anthropology and in other disciplines, since 1975. The theoretical roots and implications of constructionist theory are explored.The intensifying competition between cultural influence and constructionist paradigms has been altered by the appearance of AIDS and the subsequent increased support for research on sexuality. On the one hand, the expansion in funding threatens to strenghten essentialist models in biomedical contexts and cultural influence models in anthropology. On the other hand, the complexities and ambiguities inherent in the sexuality under study may both reveal the strengths of constructionist approaches and spur the development of research and theory in anthropology.